Comparing phosphorus recovery and optimum time digestion from single and mixing substrates by using anaerobic mesophilic digestion technique / Selaman R. and Wid N. - Selaman, Rafidah; Wid, N. (Universiti Teknologi MARA, Sabah, 2023)
Phosphorus (P) is considered a limited and non-renewable mineral source that is essential in our daily lives, especially for the agricultural industry to produce fertilizer. Food Waste (FW), Palm Oil Mill Effluent Sludge (POMES), and Water Treatment Sludge (WTS) are wastes that are claimed to contain nutrients such as P. One of the methods that can be used to recover P is through the Anaerobic Mesophilic Digestion (AMD) technique. Therefore, this study was carried out to investigate the highest P recovery and time digestion from single and mixing substrates. The physicochemical and biological properties of raw FW, POMES, and WTS were determined, and it was reported that wastes were suitable to undergo the AMD process. Mesophilic conditions 350C (±1) were used as the appropriate conditions for the anaerobic bacteria (AB) to reproduce and grow. Results for single substrates found that POMES recovered the highest P with 57.88% (±1.24), and optimum digestion was at day 12. While FW and WTS recovered P with 31.94% (±0.76) and 26.47% (±1.51), respectively, the optimum digestion times for both wastes were at days 18 (FW) and 21 (WTS), respectively, which were longer than POMES. In mixing substrates, FW-POMES contributed to the highest P recovery value with 68.34% (±1.49), and the optimum time digestion was on day 9. Followed by WTS-POME, FW-WTS, and FW-POMES-WTS with values of 60.42% (±2.12) (day 15), 48.05% (±2.51) (day 8), and 20.85% (±1.33) (day 3), respectively. The better synergetic effect within anaerobic bacteria (AB) in mixing substrates with FW-POMES could eventually influence the highest P removal from the substrate in a short period of time. Moreover, this study also provides information on new strategies used in recovering P.